PENDEKATAN KURATIF GURU AL-ISLAM DALAM MENANGANI TINDAK BULLYING DI SMPM 44 PAMULANG TANGERANG SELATAN - Wardoyo, Verrel; Busahdiar (STKIP Subang, 2026)
This study aims to analyze the curative approach implemented by Al-Islam teachers in addressing bullying at Muhammadiyah 44 Junior High School in Pamulang, South Tangerang. The background of this study is based on the persistence of bullying behavior in the school environment, both verbal, nonverbal, and social, which negatively impacts students' psychological and social well-being. The research method used was qualitative with a descriptive approach. Primary data sources were obtained from Al-Islam teachers, the principal, and five students directly or indirectly involved in the bullying cases. Secondary data sources came from a study of school documents and relevant previous research findings. Data collection techniques included observation, in-depth interviews, and document review. Data analysis was conducted through the stages of data collection, data reduction, data presentation, and drawing conclusions or verifying and testing credibility using the triangulation method. The results of the study indicate that: (1) the implementation of Al-Islam teachers' curative approach is carried out systematically, emphasizing moral development, a persuasive approach, and an understanding of Islamic values. (2) the impact of the curative approach is carried out through individual guidance such as students becoming more open and easily directed in changing attitudes and behavior in a positive direction, mediation between perpetrators and victims such as teacher assistance as mediators, providing religious advice such as through instilling Islamic moral values ​​that encourage students' moral awareness and changes in behavior in a more positive direction, as well as ongoing coordination between homeroom teachers and schools such as through joint monitoring and intensive communication regarding the development of student behavior. (3) supporting factors include support from school policies, religious culture, while inhibiting factors include the influence of the social environment, low awareness of some students, and the limited role of parents.